Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00264-020-04799-0
|View full text |Cite
|
Sign up to set email alerts
|

Change in the weight-bearing line ratio of the ankle joint and ankle joint line orientation after knee arthroplasty and high tibial osteotomy in patients with genu varum deformity

Abstract: Purpose Several studies reported that excessive correction of severe genu varum deformity with total knee arthroplasty or high tibial osteotomy (HTO) could result in ankle joint pain and osteoarthritis progression. However, few studies have evaluated the change in the weight-bearing-line (WBL) ratio of the ankle joint after knee arthroplasty or HTO in patients with genu varum deformities. This study aimed to investigate the change in the WBL ratio of the ankle joint and ankle joint line orientation after knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 21 publications
2
37
1
Order By: Relevance
“…This work was based on the idea that a change of the weight-bearing line at the knee could alter the coronal orientation of the ankle. Given that a long leg standing X-ray is performed with the knees pointing forward, it can be deduced that the X-ray represents a natural illustration of a standing position of the lower extremity [17][18][19][20]. Therefore, one must understand that for an even foot sole contact with the ground after valgisation or varisation osteotomy around the knee, the joints distal to the talus (mainly the subtalar joint) have to adapt by inversion or eversion.…”
Section: Discussionmentioning
confidence: 99%
“…This work was based on the idea that a change of the weight-bearing line at the knee could alter the coronal orientation of the ankle. Given that a long leg standing X-ray is performed with the knees pointing forward, it can be deduced that the X-ray represents a natural illustration of a standing position of the lower extremity [17][18][19][20]. Therefore, one must understand that for an even foot sole contact with the ground after valgisation or varisation osteotomy around the knee, the joints distal to the talus (mainly the subtalar joint) have to adapt by inversion or eversion.…”
Section: Discussionmentioning
confidence: 99%
“…Elson et al 11 presented the case of a patient with medial ankle pain and lateral instability in whom an HTO was performed, resulting in significant resolution of the ankle symptoms. Recently, Kim et al 12 reported that the correction of a knee varus deformity with HTO or TKA might improve the symptoms of medial ankle arthritis but could worsen lateral ankle arthritis. These reports corresponded to improvements in the symptoms of medial osteoarthritis in the ankle joint following HTO in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment methods for post-traumatic ankle arthritis include conservative treatment [4], arthroscopic surgery [14], osteotomy around the ankle [21], ankle distraction arthroplasty [22], ankle arthrodesis [14][23], total ankle arthroplasty [24], and combined internal and external xation surgery [12]. However, the optimal treatment remains unclari ed.…”
Section: Discussionmentioning
confidence: 99%